Study on games content and effectiveness of universal action at senior level - Division A - Cojocaru, A. M.; Cojocaru, M. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
The study with the title Study about the contain of games and the efficiency shares of the universal players to the senior level, consisted in the analyzes of the model of the game through modification appeared in the contain of the game competition current: the speed accelerated of game, the development of power of attack, execute of serve and the block, but and the specific peculiarities of reception and the attack, due modifications in main the new changes supervened in regulations. Making an accurate analysis of the content in accordance with reality racing game can give us a large amount of accurate information on the game of volleyball player called in slang "falsely elevated" senior division at A1, available that can provide benchmarks and absolutely essential necessary to prepare players for this post and also the development of a model-based game in November. Determination of the game must bring their contribution to the knowledge of volleyball practice at this stage, reference is internal competition in the reality game. Assuming that the game of volleyball takes place after certain fundamental characteristics and effectiveness of the fund request of the players that make team play features printed pattern preparation, determine the game stations, and the default position of the player in two zone, it becomes necessary to increase the objective parameters that can play the whole team